Persepsi Guru Mengenai Pembelajaran Ips Pada Masa Pandemi Menggunakan Media Audio Visual (Penelitian Survey Dalam Meningkatkan Karakter Disiplin Peserta Didik Dengan Metode Deskriptif Kuantitatif Terhadap Guru Di Sumedang Selatan) - Sari, Reni Wulan; Kurnia, Dadang; Aeni, Ani Nur (Jurnal Pena Ilmiah, 2021)
The existence of limitations in teaching and learning should not make teachers lose the opportunity to develop methods and learning strategies that are carried out. During the COVID-19 pandemic, the character formation of students must still be considered. The use of media during learning can help teachers deliver material and audio-visual media is one of the learning media that can be used. The purpose of the studyawas to determine the understanding and assessment of teachers in implementing social studies learning using audio-visual media to improve the disciplined character of students during the pandemic. The research method uses descriptive quantitative with a survey research design. The population of the study was an "A" accredited elementary school teacher in Sumedang District using a questionnaireainstrument. The results showed that the teacher's understanding in carrying out social studies learning based on audio-visual media to improve the disciplined character of students during the pandemic was very good. The teacher's assessment of audio-visual media in developing the disciplined character of students in social studies subjects during the pandemic is very good.